If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9y + 8)(7y + 26) = 0 Reorder the terms: (8 + 9y)(7y + 26) = 0 Reorder the terms: (8 + 9y)(26 + 7y) = 0 Multiply (8 + 9y) * (26 + 7y) (8(26 + 7y) + 9y * (26 + 7y)) = 0 ((26 * 8 + 7y * 8) + 9y * (26 + 7y)) = 0 ((208 + 56y) + 9y * (26 + 7y)) = 0 (208 + 56y + (26 * 9y + 7y * 9y)) = 0 (208 + 56y + (234y + 63y2)) = 0 Combine like terms: 56y + 234y = 290y (208 + 290y + 63y2) = 0 Solving 208 + 290y + 63y2 = 0 Solving for variable 'y'. Factor a trinomial. (26 + 7y)(8 + 9y) = 0Subproblem 1
Set the factor '(26 + 7y)' equal to zero and attempt to solve: Simplifying 26 + 7y = 0 Solving 26 + 7y = 0 Move all terms containing y to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + 7y = 0 + -26 Combine like terms: 26 + -26 = 0 0 + 7y = 0 + -26 7y = 0 + -26 Combine like terms: 0 + -26 = -26 7y = -26 Divide each side by '7'. y = -3.714285714 Simplifying y = -3.714285714Subproblem 2
Set the factor '(8 + 9y)' equal to zero and attempt to solve: Simplifying 8 + 9y = 0 Solving 8 + 9y = 0 Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 9y = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 9y = 0 + -8 9y = 0 + -8 Combine like terms: 0 + -8 = -8 9y = -8 Divide each side by '9'. y = -0.8888888889 Simplifying y = -0.8888888889Solution
y = {-3.714285714, -0.8888888889}
| a^3+10a^2+25a= | | (9y+8)(8y+26)=0 | | 3m+2m+4n= | | -31+6x=2x+27 | | (3/4)p=18 | | 6(1+103x)=9 | | -16-2x=8-6x | | 2+3a=2(1-a) | | -28+44=x+13 | | 7n+9n= | | 2(6-5x)=-20+6x | | (6/11)=9x | | 4x-27=44-3x | | x*0.9=33.33 | | 5x+5-7(x+1)=6x+3 | | 3x-6x+5=x-7+12 | | -4(n-2)-2=5-3n | | x+(x*0.9)=33.33 | | 4(1+5n)=-28+4n | | 24/80=30/100 | | 6(w+1)-10=4(w-1)-2w | | 1.2=(x/x-50) | | 10+6r=4(1+2r) | | 4x+70=8x+110 | | 1.2=x/x-50 | | -28-4x=4(1-5x) | | -7(x/3-10)=91 | | m=a/s | | 3.7=z/4 | | 7(x+1)-1=32 | | -3x^2+24x^2-48x= | | 5x^2-28x-240=0 |